DEVELOPING WOMEN AND CHILD FRIENDLY VILLAGES THROUGH PARENTING SOCIALIZATION EFFECTIVE COMMUNICATION BETWEEN PARENTS AND CHILDREN IN THE DIGITAL ERA - Haris Khoironi, Ahmad; An Nasser, Ababil; Faqih Almuzakky, Muhammad; Zusril , Mokhamad; Amelia Nurma Dewi, Lailatul; Ayu Firnanda, Faradillah; Vanessa Amanda, Layly, Dea; Saskiya Rohmah, Lavina; Nihayatul Maghfiroh, Nelly; Qoriatul Humaida , Zulfa; Syifa , Fadilatus; Setiorini, Intan; et al. (Proceedings of Annual Conference on Community Engagement, 2024)
The aim of this community service initiative is to provide mothers and children with an understanding of optimal and useful communication so that monitoring of children’s development can be properly achieved. The research method applied is participatory action research (PAR), which, based on analysis of findings from the field, shows that adopting effective communication patterns is very essential for parents and children as a form of prevention against the negative impact of gadget use on children’s learning and behavior. The results of this activity showed a very positive response from the participants, who considered this activity to be very relevant to current parenting needs, especially regarding the importance of communicating in an effective way to provide a sense of appreciation and attention to children. By implementing effective communication, problems related to children’s learning and behavior can be monitored and resolved properly.